A sub 1-volt subthreshold bandgap reference at the 14 nm FinFET node. (September 2018) - Prilenski, Lucas; Mukund, P.R.
Abstract: As supply voltages continue to decrease, it becomes harder to ensure that the voltage drop across a diode connected BJT is sufficient enough to conduct current without sacrificing die area. One such solution to this potential problem is the diode connected FinFET operating in weak inversion. In addition to conducting appreciable current at voltages significantly lower than the power supply, the diode connected FinFET reduces the total area for the bandgap implementation. A 14 nm bandgap reference was created and simulated across Monte Carlo for 100 runs at nominal supply voltage and 10% variation of the power supply in either direction. The average temperature coefficient was measured to be 153.6 p p m C ° and the voltage adjustment range was found to be 204.1 mV. The two FinFET subthreshold diodes consume approximately 2.8% of the area of the BJT diode equivalent. Utilizing an appropriate process control technique, subthreshold bandgap references have the potential to overtake traditional BJT based bandgap architectures in low power, limited area applications.